Tekstowe funkcje dwukropka – na przykładzie "Dziejów w Koronie Polskiej" Łukasza Górnickiego - Kinga Tutak (Ksiegarnia Akademicka Publishing, 2017)
Textual Functions of the Colon: Using the Example of Łukasz Górnicki’s Dzieje w Koronie Polskiej The paper analyses the textual functions of the colon in 1637–1855 editions of Łukasz Górnicki’s Dzieje w Koronie Polskiej. The colon, as an element of rhetoric-intonational punctuation, served to organize and to adequately manage the textual matter. In 19th c. editions of Dzieje…, we observe a snuffing out of textual functions of the colon, in connection with the transition to the syntactic-logical punctuation.